EDUCATIONAL OUTREACH ON LITERACY FOR TPQ BUSTANUL ULUM SEJATI STUDENTS IN THE MAPAK BELATUNG AREA MATARAM - Sukardi; M. Afan; Nurul Wahidah; Anisa Nur’aini (PT. Jurnal Center Indonesia Publisher, 2025)
The unrestricted use of mobile phones by elementary school children to access social media and online games can be disastrous for them. This greatly affects their literacy skills, leading to suboptimal development of the four language skills: listening, speaking, reading, and writing. This community service program aims to raise awareness and motivate the students of TPQ Bustanul Ulum Sejati to improve their literacy skills. The method used in this community service activity was lectures and discussions. The activity received a positive response from the TPQ Bustanul Ulum Sejati students and their parents. The program was conducted through material presentations and discussions using a relaxed conversational approach, making the activity feel less formal and more comfortable. This atmosphere allowed all the students to express their opinions without hesitation. This activity left a positive impression on the participants about the importance of literacy and avoiding excessive use of mobile phones to access social media and online games.